Procesos didácticos y aprendizaje significativo del área de matemática en estudiantes de la Institución Educativa N° 60078 Yraida Rojas Regra, Pebas 2024 - Vela Sanchez, Jenyfer (2025)
The general objective was to determine the relationship between the didactic processes and the significant learning in mathematics of the students of the Educational Institution No. 60078 Yraida Rojas Regra de Pebas. The study was correlational in scope with a non-experimental, cross-sectional and bivariate design. The population and sample consisted of 123 students. The most relevant result reflects a statistically significant relationship between didactic processes and meaningful learning in mathematics, with a Kendall's Tau B coefficient of 0.673 (p<0.001), thus validating the main hypothesis. Among the dimensions analyzed, reflection and transfer presented the highest correlation with significant learning (Kendall's Tau B =0.682; p<0.001). It was concluded that didactic processes play a key role in promoting meaningful learning, highlighting the importance of the dimensions of understanding the problem, representation and formalization, and reflection and transfer in the development of mathematical competencies.